Personality traits and learning effectiveness in online vocational education: Insights from international students in high-tech learning contexts in China - Li, Lanxin; Baba Rahim, Norizan (Journal of International Students, 2026)
This study examines how personality traits influence learning effectiveness in online vocational education among international students in China, with attention to the mediating role of online learning self-efficacy and the moderating role of perceived high-tech learning support. Using a mixed-method design, survey data were collected from 412 international students enrolled in online or blended vocational programs. Measures included personality traits (conscientiousness and openness), online learning self-efficacy, perceived high-tech learning support, and learning effectiveness. A PLS-SEM-inspired path model with bootstrapping tested direct, indirect, and interaction effects, supplemented by 18 semi-structured interviews. Results indicate that personality traits positively predict self-efficacy and learning effectiveness, with self-efficacy partially mediating this relationship. Perceived high-tech learning support strengthens the link between self-efficacy and learning effectiveness. Interview findings underscore the role of simulation-based practice, timely feedback, and multilingual guidance in enhancing confidence and skill development.